Tubuloglomerular Disease With Cone-Shaped Epiphyses Associated With Hypomorphic Variant and a Novel p.Cys14Arg in the TTC21B Gene: A Case Report - Bezdíčka, Martin; Zemková, Dana; Skálová, Sylva; Hovorková, Eva; Podhola, Miroslav; Burkert, Jan; Zieg, Jakub (Frontiers in Pediatrics, 2021)
Monogenic nephrotic syndrome is associated with a resistance to initial glucocorticoid therapy and causative variants, which may be found in several genes influencing podocyte stability and kidney development. The TTC21B gene, which encodes the retrograde intraflagellar transport protein IFT139, is found mostly in association with ciliopathies in humans. The role of this protein in podocyte cytoskeleton stability was confirmed later and the mutated TTC21B may be also associated with proteinuric diseases, such as nephrotic syndrome. Our patient manifested as an infant with brachydactyly, nephrotic-range proteinuria and renal tubular acidosis, and a kidney biopsy revealed focal segmental glomerulosclerosis. Multiple phalangeal cone-shaped epiphyses of the hand were seen on x-ray. Next-generation sequencing revealed the well-described p.Pro209Leu heterozygous variant and a novel heterozygous p.Cys14Arg variant in the TTC21B gene. Our finding confirmed that the causative variants in the TTC21B gene may contribute to a spectrum of clinical features, such as glomerular proteinuric disease with tubulointerstitial involvement and skeletal abnormalities.